Recent advances in gelatin-based therapeutics. (3rd August 2019) - Echave, Mari Carmen; Hernáez-Moya, Raquel; Iturriaga, Leire; Pedraz, José Luis; Lakshminarayanan, Rajamani; Dolatshahi-Pirouz, Alireza; Taebnia, Nayere; Orive, Gorka
ABSTRACT: Introduction : Biomaterials have provided a wide range of exciting opportunities in tissue engineering and regenerative medicine. Gelatin, a collagen-derived natural biopolymer, has been extensively used in regenerative medicine applications over the years, due to its cell-responsive properties and the capacity to deliver a wide range of biomolecules. Areas covered : The most relevant properties of gelatin as biomaterial are presented together with its main therapeutic applications. The latter includes drug delivery systems, tissue engineering approaches, potential uses as ink for 3D/4D Bioprinting, and its relevance in organ-on-a-chip platforms. Expert opinion : Advances in polymer chemistry, mechanobiology, imaging technologies, and 3D biofabrication techniques have expanded the application of gelatin in multiple biomedical research applications ranging from bone and cartilage tissue engineering, to wound healing and anti-cancer therapy. Here, we highlight the latest advances in gelatin-based approaches within the fields of biomaterial-based drug delivery and tissue engineering together with some of the most relevant challenges and limitations.